Fatigue performance of butt-welded austenitic stainless-steel joints evaluated by peak-stress method. (1st February 2022) - Pan, Chunyu; Dai, Zhen; Xue, Jian; Peng, Yang; Dong, Jun
Abstract: In this study, the fatigue performance of butt-welded austenitic stainless-steel joints is investigated by fatigue test, nominal-stress method and peak-stress method. Welding profiles and misalignment were analyzed, residual stresses were measured, and fatigue tests were conducted. The experimental fatigue data are regressed to the stress range versus life-to-failure ( S–N ) curve of the nominal stress method, and the factor affected dispersion is analyzed by using the peak-stress method. The following conclusion can be drawn: (1) The fatigue strength is 155 MPa in nominal stress method, which is higher than that of structural steel (80 MPa) in the international fatigue design standards. (2) The influence of the welding misalignment and distortion can be accurately estimated by the combing the reference S-N curve and stress magnification factor formulae from the international fatigue design standards.